Addictive consumption, imperfect substitutes and self control: A model and an application to slot machines - Claudio Deiana; Davide Dragone; Ludovica Giua (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
We propose a model of addictive consumption to study the demand for imperfect substitutes involving substances like alcohol, nicotine and opioids, as well as behavioral addictions like gambling and digital addiction. We study a 2017 Italian policy aimed at reducing gambling by limiting the number of available slot machines. Despite the reduction in slot machines, the policy produced an unintended 25% increase in net expenditure, particularly among low-wealth and low-educated individuals who also engage in other addictive behaviors. This result can be rationalized as the consequence of changes in self-control costs due to social contagion effects.
Keywords: I18; L43; L83; 330; Addiction; Gambling; Horizontal differentiation; Self-control; Slot machines; Temptation